(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
AI is exponentially incrementing its relevance within contemporary societies. Legal systems are absolutely not exempt from this phenomenon. The essay stresses the need of what is called proactive regulation, as a complementary approach to the reactive regulation, that risk to look weary in front of AI. According to the specific perspective of the analysis, the proposed approach consists also in a better integration between law and other regulatory systems. The analysis develops toward: the concept of “technological neutrality”, the relationships between ethics and law, looking at the role of self-regulation; the relationships between technology and law, looking at the role of co-regulation; the normative straight of code; the request of more flexible and innovative normative tools for AI.